2003
DOI: 10.1002/ange.200351996
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of an Atropdiastereomer of RP‐66453 and Determination of Its Absolute Configuration

Abstract: Die absolute Konfiguration des Naturstoffs RP‐66453 (1) wurde durch Totalsynthese seines Atropdiastereomers und spektroskopische Studien beider Verbindungen zu aR, S, S, S, S, S bestimmt. Eine SNAr‐basierte cyclische Etherbildung und eine intramolekulare atropdiastereoselektive Suzuki‐Miyaura‐Kupplung wurden zum Aufbau des schwer zugänglichen bicyclischen A‐B‐O‐C‐Gerüsts von RP‐66453 genutzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The [PdA C H T U N G T R E N N U N G (PPh 3 ) 4 ]-catalyzed intramolecular Suzuki-Miyaura coupling reaction of compound 19 efficiently gave cyclodityrosines 20 and 20' in 50 % and 14 % yields, respectively. [24] Although the 1 H, 13 C, and 2D NMR data could not distinguish the structural differences between compounds 20 and www.chemeurj.org 20', owing to line broadening of the signals and their complexity caused by cis/trans isomerization of the tertiary amide bond, we tentatively assigned compounds 20 and 20' to be atropisomers. Although a biphenyl axis usually requires three or four ortho substituents for its conformers to become atropisomers, [25] their 12-membered ring structure and the two bulky benzyloxy groups might provide sufficient steric hindrance to the rotation about the CÀC biphenyl bond.…”
Section: Wwwchemeurjorgmentioning
confidence: 84%
“…The [PdA C H T U N G T R E N N U N G (PPh 3 ) 4 ]-catalyzed intramolecular Suzuki-Miyaura coupling reaction of compound 19 efficiently gave cyclodityrosines 20 and 20' in 50 % and 14 % yields, respectively. [24] Although the 1 H, 13 C, and 2D NMR data could not distinguish the structural differences between compounds 20 and www.chemeurj.org 20', owing to line broadening of the signals and their complexity caused by cis/trans isomerization of the tertiary amide bond, we tentatively assigned compounds 20 and 20' to be atropisomers. Although a biphenyl axis usually requires three or four ortho substituents for its conformers to become atropisomers, [25] their 12-membered ring structure and the two bulky benzyloxy groups might provide sufficient steric hindrance to the rotation about the CÀC biphenyl bond.…”
Section: Wwwchemeurjorgmentioning
confidence: 84%
“…[36] With the properly functionalized tripeptides 21 and 22 in hand, we set out to examine the desired macrocyclization by intramolecular Suzuki-Miyaura reaction (Table 1). [22,23,37] The inherent need for a base in such cross-coupling reactions poses an epimerization problem. [38] It was assumed that the presence of the unprotected phenol could minimize the epimerization of 21.…”
Section: Resultsmentioning
confidence: 99%
“…Realizing that these cyclizations were generally low yielding and/or not compatible with peptidic structures, our group has been working on the intramolecular SuzukiMiyaura reaction [22] for macrocycle formation and has accomplished total syntheses of a number of natural products with an endo aryl-aryl bond. [23] Recently, Romesberg et al [5] and our group [24] independently reported total syntheses of arylomycin A 2 (1) with similar strategies. As a continuation of this research program, we became interested in the synthesis of arylomycins B because they display greater antibacterial activity than the A series.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the presence of an N-Boc group may lead to a conformation that disfavors the ring closure, we prepared 14 b by coupling of 12 with 13 b (P 1 = H). To our delight, the intramolecular Suzuki-Miyaura reaction [23] cyclophane 15, together with a small amount of partially Odesilylated compound 16, in 66 % yield. The axial chirality of 15 was determined to be aR by detailed NOE studies (see the Supporting Information) as well as from the characteristically upfield shift of the a proton of amino acid F (d = 4.2 ppm).…”
mentioning
confidence: 97%